2023
DOI: 10.1002/advs.202204006
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Metabolism Acts as a New Anti‐Ferroptotic Pathway to Mediate Tumor Growth

Abstract: Emerging evidence reveals that amino acid metabolism plays an important role in ferroptotic cell death. The conversion of methionine to cysteine is well known to protect tumour cells from ferroptosis upon cysteine starvation through transamination. However, whether amino acids‐produced metabolites participate in ferroptosis independent of the cysteine pathway is largely unknown. Here, the authors show that the tryptophan metabolites serotonin (5‐HT) and 3‐hydroxyanthranilic acid (3‐HA) remarkably facilitate tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Alteration of metabolism has been increasingly linked to change of cell susceptibility to cell death. Multiple lines of evidence support this notion in the lipid peroxidation associated cell death, known as ferroptosis 16,19,29 . Among various metabolic cues that regulate ferroptosis, lipid metabolism, in particular, fatty acid metabolism has been most intensively investigated.…”
Section: Discussionmentioning
confidence: 92%
“…Alteration of metabolism has been increasingly linked to change of cell susceptibility to cell death. Multiple lines of evidence support this notion in the lipid peroxidation associated cell death, known as ferroptosis 16,19,29 . Among various metabolic cues that regulate ferroptosis, lipid metabolism, in particular, fatty acid metabolism has been most intensively investigated.…”
Section: Discussionmentioning
confidence: 92%
“…However, iron is an essential element for many fundamental physiological activities, and chelation iron by deferoxamine may increase the risk of iron imbalance (35,36). Vitamin K, serotonin (5-hydroxytryptamine), 3-hydroxyanthranilic acid, Fer-1, and liproxstatin-1 were found to inhibit ferroptosis by acting as potent RTAs (37)(38)(39), suggesting that these compounds may have a wide range of antioxidant effects. In addition, itaconate, quercetin, and resveratrol have been found to inhibit ferroptosis via defense against oxidative stress (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…KYNU is widely expressed in nearly all organs of the body, with particularly elevated levels observed in the liver, urinary bladder, and appendix. 50 KYNU is involved in various inflammatory skin diseases, [51][52][53][54][55] cardiovascular diseases, 56 inflammatory bowel disease, 57,58 and several types of cancers, [59][60][61][62][63] exerting its effects through diverse pathways. While previous studies have indicated abnormalities in tryptophan metabolism within HS lesions, 18 there is currently a scarcity of research confirming the distinctive expression pattern of KYNU specifically in HS.…”
Section: Discussionmentioning
confidence: 99%